2018
DOI: 10.1590/1676-0611-bn-2017-0422
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of the metazoan parasites of Prochilodus lineatus (Valenciennes, 1837) (Characiformes: Prochilodontidae) in anthropized environments from the Batalha River, São Paulo State, Brazil

Abstract: Biodiversity of fish parasites is a field of significant growth worldwide, whether due to the advancement of fish farms or the important role of these organisms as indicators of environment quality and ecosystem health, making them useful tools in the conservation and maintenance of the biodiversity as a whole. The objectives of this study were to evaluate the structure and composition of the parasitic fauna of Prochilodus lineatus collected from two structurally distinct stretches of the Batalha River. Fifty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
3
3
0
1
Order By: Relevance
“…The richness accumulation curve of the observed species and the richness estimator did not reach the asymptote, following the same patterns found in studies carried out by Gião et al (2020), Pelegrini et al (2018), and Leite et al (2018) with other hosts, and with H. malabaricus in the same region where the Jacaré-Pepira River is inserted. This may be an indicator that even with a larger number of hosts analyzed and with new studies such as that of Lehun et al (2020), who identified and classified 315 parasite taxa, of which 201 were identified at species level, the biodiversity of the parasitic communities in rivers of the Upper Paraná River basin is not yet fully known, which intensifies the importance of studies on the characterization of ichthyofauna for that region.…”
Section: Discussionsupporting
confidence: 83%
“…The richness accumulation curve of the observed species and the richness estimator did not reach the asymptote, following the same patterns found in studies carried out by Gião et al (2020), Pelegrini et al (2018), and Leite et al (2018) with other hosts, and with H. malabaricus in the same region where the Jacaré-Pepira River is inserted. This may be an indicator that even with a larger number of hosts analyzed and with new studies such as that of Lehun et al (2020), who identified and classified 315 parasite taxa, of which 201 were identified at species level, the biodiversity of the parasitic communities in rivers of the Upper Paraná River basin is not yet fully known, which intensifies the importance of studies on the characterization of ichthyofauna for that region.…”
Section: Discussionsupporting
confidence: 83%
“…This dominance also can be explained by the feeding habits of the host, which includes a wide variety of invertebrates, presenting low food specificity, making it extremely susceptible to parasite acquisition through the trophic web (Fugi et al, 2001;Lizama et al, 2005). Other studies have already demonstrated the high prevalence of N. curemai in P. lineatus (Martins et al, 2001;Leite et al, 2018;Duarte et al, 2020;Lehun et al, 2020), which contributes to the high abundance in the present study, especially for Period 2.…”
Section: Discussionsupporting
confidence: 69%
“…In the study by Pedro et al (2016) with Acestrorhynchus lacustris (Lütken, 1875), this pattern was also observed (H = 1.42; D = 1.28; J = 0.75). As the present study, Leite et al (2018) in an analysis of Prochilodus lineatus (Valenciennes, 1837), obtained greater Margalef Index (1.83) than diversity (0.81). Although lower than the other two indexes, Pielou's equitability values are not considered low, since this index varies from 0 to 1, different from the other indexes that do not have this limitation.…”
Section: Discussionsupporting
confidence: 62%
“…The Batalha River, despite presenting a diverse ichthyofauna (Santos and Heubel, 2008), has been the target of few studies involving ecological analyzes of parasitic fish communities (Pedro et al, 2016;Leite et al, 2018;Negrelli et al, 2018;Pelegrini et al, 2021). Thus, this study aimed to inventory the parasitic fauna of H. littorale specimens from the Batalha River, São Paulo, Brazil, as well as to present considerations on the composition and structure of the parasitic communities present in this host.…”
Section: Introductionmentioning
confidence: 99%